Inequalities of Hardy type for Jackson Nörlund Integrals - Ashraf, Naheed; Khan, Khuram Ali; Mobeen, Shakila; Nosheen, Ammara (Communications in Mathematics and Applications, 2018)
In the paper, we prove Jensen's inequality for Jackson Nörlund integrals, and by using Jensen's inequality, Hardy type inequalities with general kernels as well as choosing special kernels are proved. In seek of applications to these inequalities we give Hilbert-Hardy inequality and Polya-Knop type inequalities.